A customer satisfaction model for a utility service industry - Jamil, Jastini; Mohd Nawawi, Mohd Kamal; Ramli, Razamin (2016)
This paper explores the effect of Image, Customer Expectation, Perceived Quality and Perceived Value on Customer Satisfaction, and to investigate the effect of Image and Customer Satisfaction on Customer Loyalty of mobile phone provider in Malaysia.The result of this research is based on data gathered online from international students in one of the public university in Malaysia. Partial Least Squares Structural Equation Modeling (PLS-SEM) has been used to analyze the data that have been collected from the international students’ perceptions.The results found that Image and Perceived Quality have significant impact on Customer Satisfaction.Image and Customer Satisfaction ware also found to have significantly related to Customer Loyalty. However, no significant impact has been found between Customer Expectation with Customer Satisfaction, Perceived Value with Customer Satisfaction, and Customer Expectation with Perceived Value. We hope that the findings may assist the mobile phone provider in production and promotion of their services.